2018
DOI: 10.1016/j.leukres.2018.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic hematopoietic stem cell transplantation for the treatment of BCR-ABL1-negative atypical chronic myeloid leukemia and chronic neutrophil leukemia: A retrospective nationwide study in Japan

Abstract: Atypical chronic myeloid leukemia (aCML) and chronic neutrophilic leukemia (CNL) are rare BCR-ABL1 fusion gene-negative myeloid neoplasms with a predominance of neutrophils. Since no standard therapeutic strategy currently exists for these diseases, we retrospectively evaluated the outcomes of allogeneic hematopoietic stem cell transplantation (allo-HSCT) for aCML and CNL. Data from 14 aCML and 5 CNL patients as their diagnoses were collected using a nationwide survey. Allo-HSCT was performed between 2003 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…Currently, the only known treatment that has relatively better outcomes in disease free survival in aCML patients is allogeneic hematopoietic stem cell transplantation (HSCT). 27 Unfortunately, HSTC cannot be an option for all patients in LMICs because of lack of suitable donor, advanced age, socioeconomic constraints and specialized medical teams. 8,17,28,29 Additionally the cost of stem cell transplant and immunosuppressant drug costs (taken after transplant) approximates to 3–4 million Pakistani rupees (on average) and becomes an additional challenge for economically deprived populations.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the only known treatment that has relatively better outcomes in disease free survival in aCML patients is allogeneic hematopoietic stem cell transplantation (HSCT). 27 Unfortunately, HSTC cannot be an option for all patients in LMICs because of lack of suitable donor, advanced age, socioeconomic constraints and specialized medical teams. 8,17,28,29 Additionally the cost of stem cell transplant and immunosuppressant drug costs (taken after transplant) approximates to 3–4 million Pakistani rupees (on average) and becomes an additional challenge for economically deprived populations.…”
Section: Discussionmentioning
confidence: 99%
“…A myeloablative regimen was used in 11/14 patients. Among patients with neutrophil engraftment, 9/13 achieved a CR and the 1-year OS was 54.4%, being higher in univariate analysis in patients with related donors, <5% myeloblasts in the peripheral blood, and a Karnofsky performance status of ≤80% ( 48 ).…”
Section: Treatment Approaches For Acmlmentioning
confidence: 99%
“…124 A contemporary retrospective study of allo-HSCT in Japan reported data from 14 aCML and five CNL patients transplanted between 2003 and 2014. 142 The majority received myeloablative preconditioning regimens. Transplants were principally from alternative donors (n = 14) versus HLA-matched related (n = 5).…”
Section: Induction Chemotherapymentioning
confidence: 99%